Efficient synthesis of diversely substituted pyrazolo[1,5-a]pyrimidine derivatives promoted by ultrasound irradiation in water and their antibacterial activities - Das, Susma; Khanikar, Shilpika; Kaping, Shunan; Roy, Jayanti Datta; Sen, Arnab; Helissey, Philippe; Vishwakarma, Jai Narain (European Journal of Chemistry, 2020)
A green synthetic route leading to the discovery of a series of diversely substituted pyrazolo[1,5-a]pyrimidines, having CO2Et group embedded at position-2 has been unraveled in this article. A series of formylated active proton compounds that were chosen to react with a carboxylate substituted-3-aminopyrazole under ultrasonic irradiation in the presence of a mild acid as a catalyst and aqueous ethanol medium afforded the desired products. The molecular structures of all these synthesized compounds were established by their spectral and analytical data. A model molecule 3d, subjected to single-crystal X-ray crystallography analysis further confirms their molecular structure. The crystal crystallized to a monoclinic cell with P21/c space group, a = 7.468 (5) Å, b = 27.908 (17) Å, c = 7.232 (4) Å, β = 104.291 (7)o, V =1460.7(15) Å3, Z = 4, μ(MoKα) = 0.096 mm-1, Dcalc = 1.352 Mg/m3 16667 measured reflection (5.63 ≤ 2Θ ≤ 57.57°), 3720 unique (Rint = 0.0965, Rsigma = 0.0945) which were used in all calculations. The final R1 was 0.0750 (I > 2σ(I)) and wR2 was 0.2226 (all data). These compounds were further explored for their antibacterial potential, and a few of them have exhibited encouraging results.